2012
DOI: 10.4314/ajpsy.v15i2.14
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depressive symptoms among adolescents in Nairobi public secondary schools: association with perceived maladaptive parental behaviour

Abstract: Objective: Depression in adolescents is a matter of concern because of its high prevalence, potential recurrence and impairment of functioning in the affected individual. The study sought to determine the prevalence of depressive symptoms among adolescents in Nairobi (Kenya) public secondary schools; make a comparison between day and boarding students; and identify associated factors in this population. Method: A random sample of school going adolescents was taken from a stratified sample of 17 secondary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
76
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 47 publications
13
76
1
Order By: Relevance
“…Other studies in Africa among same aged post-secondary students produced similar findings, suggesting that test-taking and performance-based stress can increase young adults' odds for depression (Khasakhala et al, 2012;Raman and Janse van Rensburg, 2013). Students in the later stages of their education are likely to be undertaking competitive examinations that determine admission to highly competitive tertiary institutions.…”
Section: Patterns Of Misclassificationsupporting
confidence: 58%
See 1 more Smart Citation
“…Other studies in Africa among same aged post-secondary students produced similar findings, suggesting that test-taking and performance-based stress can increase young adults' odds for depression (Khasakhala et al, 2012;Raman and Janse van Rensburg, 2013). Students in the later stages of their education are likely to be undertaking competitive examinations that determine admission to highly competitive tertiary institutions.…”
Section: Patterns Of Misclassificationsupporting
confidence: 58%
“…Although previous studies worldwide vary greatly in their methodology, sufficient convergence has emerged to implicate several sociodemographic variables captured in this data set as potential risk factors for misclassification of depression (Araya et al, 1992;Chipimo and Fylkesnes, 2010;Cluver et al, 2009;Das et al, 2007;Jewkes et al, 2010;Kaggwa and Hindin, 2010;Khasakhala et al, 2012;Langhaug et al, 2010;Mavhu et al, 2013;Nyamukapa et al, 2010;Scholte et al, 2011). Studies have shown that gender, education, wealth levels, orphan status, and age can have varying effect on depression misclassification (Araya et al, 1992;Lewis and Araya, 1995;Mari and Williams, 1986;Schmiege and Russo, 2005;Whetten et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…The constructs were further factually derived into four perceived parenting behaviour dimensions: emotionally attached parent (emotionally/physically abusing and authoritarian parenting behaviour), rejecting parent (emotionally and physically neglecting parenting behaviour), under-protective parent (permissive or under-involved parenting behaviour) and adaptive parenting behaviour (authoritative parenting behaviour), which are distributed across the four scales [30,31]. This questionnaire is self-administered and has been used in Kenya in a similar age group population [32]. …”
Section: Methodsmentioning
confidence: 99%
“…In urban community settings of developing countries such as Kenya, Khasakhala et al [7] reported 26.4% as the one month prevalence of depression among 1276 adolescents in Nairobi. In Nigeria, Omigbodun et al [8] reported 12.6% as prevalence of probable depression among adolescents in rural South West Nigeria and found experiencing traumatic events as one of the predictors of depression especially when the event directly affected the youth as in sexual assault or physical abuse.…”
Section: Introductionmentioning
confidence: 99%